Robotic arm manipulator for industrial purpose - Moshi, Md. Adnan Al; Islam, Md. Eftakhairul; Cynthia, Salwa Salam (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.